A new perspective on performance persistence: evidence using portfolio holdings. (30th March 2016) - Bennett, Scott; Gallagher, David R.; Harman, Graham; Warren, Geoffrey J.; Xi, Yuki
Abstract: We investigate the existence and sources of performance persistence for Australian equity funds, using monthly portfolio holdings data. We find significant persistence among outperforming rather than underperforming funds, which is primarily related to security selection skill, and is associated with growth‐orientated funds. Meanwhile, the relation between persistence and momentum is secondary and nuanced. Further, persistence largely derives from existing holdings, while subsequent active trading contributes only moderately positive returns for both outperforming and underperforming funds. We also find that persistence fades beyond 6 months and vanishes after 24 months. Our findings differ from those for U.S. equity funds and previous Australian studies, implying that persistence may vary with market context and its identification may depend on data availability.